Educação por competências na formação profissional : um desafio para Cursos Superiores de Tecnologia no Senac-RS - Berte, Roberto Sarquis (2016)
This thesis analyzes the effectiveness of education methodology skills in professional educational institutions, especially in the Colleges of Senac-RS Technology. The growing interest in the concept of competence and its importance to education in general, including the Colleges of Technology, justifies the proposed research. It begins with an assessment of Vocational Education and legislation for Technological Education in Brazil in order to historically contextualize the empirical field, reflecting on the goals and guiding principles of Technological Level Professional Education. As a contribution to the understanding of the concept, the understanding is contemplated of the main authors who theorize about competence, to then discuss about the emergence of competence for education, its challenges and its proposals as a way to integrate different views of the actors involved in the teaching andlearning process. Finally, a survey is carried out with graduates of the Course of Technology Analysis and Systems Development, Faculty Senac Porto Alegre in order to analyze their perceptions regarding the professional skills developed in the Course of Technology and how they are these skills required by the labor market, in relation to the demands identified by companies. The results obtained by the research, as the perception of holistic character and integrated skills, the richness of the cultural context and / or professional egress is and its provisions or attitudes, may help education by competence in vocational training, especially in implementation of the challenge in Technology Colleges in Senac-RS, this benefit which may also be extended other courses of the Faculty Senac Porto Alegre and other institutions of higher education offering Colleges of Technology.